The Factors behind China’s Growing Economic Engagement in Kazakhstan and Uzbekistan in the 21st Century - Ammarah Shabbir; Amna Mahmood, (ASIAN Journal of International Peace & Security (AJIPS), 2023)
It is crucial for the states to secure and strengthen energy resources to rise and survive in international arena. The resource dependent states also require same approach. China is vigilant about politics and security nonetheless relatively more cautious in the economic sphere. The acquisition of new export markets, development of intercontinental transportation and infrastructure and safeguarding supply of natural resources are the primary motives of China. Kazakhstan and Uzbekistan are providing alternative routes to international transport corridors and a promising market for goods. China has the potential for investment, to help them build their infrastructure and new gas and oil pipelines for its own energy requirements. This study aims to analyze China’s expansion in Kazakhstan and Uzbekistan under the framework of liberalism which emphasized that liberty, equality and cooperation can be possible among states. The objective of the study is to investigate factors that motivate China’s continuous growth in these post-soviet states. This study uses qualitative method and analyzes to what extend Chinese developments are valuable for the people of Kazakhstan and Uzbekistan.